Pendidikan Kewarganegaraan Sebagai Upaya Penguatan Identitas Nasional - Daffa Salsabila; Fasha Fatimah; Intan Nuraeni; Lussy Sri A; Naufal Rifat RA (Universitas Maritim AMNI Semarang, 2023)
This paper was created with the aim of providing insight into strengthening national identity. National identity is an understanding of the identity of a nation and state, besides that the formation of national identity itself has become a provision that has been mutually agreed upon. Upholding and maintaining what already exists and trying to correct all mistakes within a nation and state. National identity consists of a collection of cultural values that develop and grow in various aspects of life. However, at this time the interaction between individuals was reduced due to the busyness of each community and the influence of globalization so as to create a society that does not care about other people and forgets about identity as a society with a nation and state. This task aims to provide efforts to strengthen national identity through civic education. We hope that this assignment can regenerate our awareness of national identity.